Pathophysiology of dyspnoea in acute pulmonary embolism: A cross‐sectional evaluation. Issue 4 (25th November 2016) - Sanchez, Olivier; Caumont‐Prim, Aurore; Riant, Elisabeth; Plantier, Laurent; Dres, Martin; Louis, Bruno; Collignon, Marie‐Anne; Diebold, Benoit; Meyer, Guy; Peiffer, Claudine; Delclaux, Christophe
ABSTRACT: Background and objective: Dyspnoea in pulmonary embolism (PE) remains poorly characterized. Little is known about how to measure intensity or about the underlying mechanisms that may be related to ventilatory abnormalities, alveolar dead space ventilation or modulating factors such as psychological modulate. We hypothesized that dyspnoea would mainly be associated with pulmonary vascular obstruction and its pathophysiological consequences, while the sensory‐affective domain of dyspnoea would be influenced by other factors. Methods: We undertook a prospective study of 90 consecutive non‐obese patients (mean ± SD age: 49 ± 16 years, 41 women) without cardiorespiratory disease. All patients were hospitalized with symptoms for <15 days and a confirmed PE (multi‐detector computed tomography (MDCT) scan, n  = 87 and high‐probability ventilation/perfusion scan, n  = 3). Patients underwent assessment of dyspnoea using the Borg score, modified Medical Research Council (mMRC) scale, assessment of psychological trait, state of anxiety and depression and chest pain via the Visual Analogical Scale at the time of maximum dyspnoea. Functional evaluations such as the quantitative ventilation–perfusion lung scan, echocardiography, alveolar dead space fraction and tidal ventilation measurements were completed within 48 h of admission. Results: Multivariate analyses demonstrated that dyspnoea was mainly linked to pulmonary vascular obstruction and/or its consequences such as raised pulmonary arterial pressure and chest pain. The sensory‐affective domain of dyspnoea showed additional determinants such as age, depression and breathing variability. Conclusion: Dyspnoea is mainly related to vascular consequences of PE such as increased pulmonary arterial pressure or chest pain. The sensory‐affective domain of dyspnoea also correlates with age, depression and breathing variability. Abstract : The pathophysiology of dyspnoea in pulmonary embolism (PE) remains poorly characterized. Our prospective study in patients with acute PE shows that, while exertional dyspnoea is mainly associated to vascular consequences of PE, the sensation of dyspnoea also correlates with factors such as age, depression and breathing variability.